X-Ray and Near-Infrared Spectroscopy of Dim X-Ray Point Sources Constituting the Galactic Ridge X-Ray Emission - Kumiko Morihana; Masahiro Tsujimoto; Ken Ebisawa (Acta Polytechnica CTU Proceedings)
We present the results of X-ray and Near-Infrared observations of the Galactic Ridge X-ray Emission (GRXE). We extracted 2,002 X-ray point sources in the Chandra Bulge Field (l =0°.113, b = 1°.424) down to ~10-14.8 ergscm-2s-1 in 2-8 keV band with the longest observation (900 ks) of the GRXE. Based on X-ray brightness and hardness, we classied the X-ray point sources into three groups: A (hard), B (soft and broad spectrum), and C (soft and peaked spectrum). In order to know populations of the X-ray point sources, we carried out NIR imaging and spectroscopy observation. We identied 11% of X-ray point sources with NIR and extracted NIR spectra for some of them. Based on X-ray and NIR properties, we concluded that non-thermal sources in the group A are mostly active galactic nuclei and the thermal sources are mostly white dwarf binaries such as cataclysmic variables (CVs) and Pre-CVs. We concluded that the group B and C sources are X-ray active stars in flare and quiescence, respectively.